Letter from James Curtis Booth to Henry Carrington Bolton, March 9, 1882 - Booth, James Curtis (1882)
James Curtis Booth (1810-1888) writes to Henry Carrington Bolton (1843-1903) an American chemist, professor of science at Trinity College, and Booth's relative. Booth declines Bolton's invitation to serve as a judge in a student essay contest.
Keywords: Booth, James Curtis, 1810-1888; Bolton, Henry Carrington, 1843-1903